MAXIMIZATION CARROT MINERALS PRESERVE AND ANTIOXIDANT CAPACITY BY FOLIAR APPLICATION OF AQUEOUS BARLEY SPROUTS EXTRACT, TREHALOSE, AND CALCIUM - Al-Khafaji, Aseel M. H. H.; Al-jubouri, Kadhim D. H. (Iraqi journal of agricultural science, 2022)
This research was implemented at vegetable field of the College of Agricultural Engineering Sciences - University of Baghdad during fall seasons, 2018 and 2019. The experiment was conducted using factorial within Randomized Complete Block Design arrangement with three factors and replicates (3X3X2). The aqueous barley sprouts extract (B0, B1) (0, 100 g.L-1) represented the first factor. Trehalose (T0, T1, T2) (0, 50, 75 mmole.L-1) represented the second factor. Calcium (C0, C1, C2) (0, 1, 2 ml.L-1) represented the third factor. The research objectives are assessing the impact of the mentioned factors and their interactions on carrot plant minerals and antioxidant accumulation. Results showed the effectiveness of three ways interaction treatment B1T2C1 in producing significant increases in phosphorus (0.302, 0.311%) total carotenoids (15.83, 15.93 mg.100-1g), β carotene (7.9, 7.967 mg.100-1g) and DPPH (97.94, 98.41%) in roots for both seasons respectively.in compare with control treatment B0T0C0.